(untitled) (Ameghiniana, 2017)
The “Irenean” is a controversial unit traditionally employed to embrace fossil vertebrates and bearing-sediments of late Neogene—roughly Pliocene—age in southern Buenos Aires Province, Argentina. Although originally intended as an intermediate unit between Montehermosan and Chapadmalalan faunas, almost a century after its description, the “Irenenean” is still poorly known. Based on fieldwork by our team during the last 25 years in its type area, the Quequén Salado River, we revisit the basic aspects of the “Irenean”. We describe the main paleontological localities and the correlations suggested by fossils and sediments and also discuss the chronology of these deposits. We conclude that the “Irenean” is a complex unit composed of at least two fossiliferous assemblages. An older assemblage is found in sediments exposed in localities downstream of the mouth of Indio Rico; a younger assemblage is contained in outcrops upstream of the mentioned point and includes the classic site of Cascada Grande. The older assemblage includes the cingulate Macrochorobates sp., the caenolestid Pliolestes tripotamicus, the tardigrade Proscelidodon cf. P. patrius and the rodent Xenodontomys ellipticus, and points to a sensu lato Huayquerian Stage/Age. The younger assemblage is typified by several taxa, including the rodents Actenomys sp. and Eumysops laeviplicatus, the argyrolagid Argyrolagus sp., the didelphid Hyperdidelphys inexpectata, the macraucheniid Promacrauchenia cf. P. chapadmalense, and the cingulate Ringueletia simpsoni, suggesting a Montehermosan Stage/Age.